The cardiac isovolumetric contraction time is an independent predictor of incident heart failure in the general population. (1st August 2020) - Alhakak, Alia Saed; Møgelvang, Rasmus; Schnohr, Peter; Modin, Daniel; Brainin, Philip; Gislason, Gunnar; Biering-Sørensen, Tor
Abstract: Background: Color Tissue Doppler imaging (TDI) M-mode through the mitral leaflet is a novel method to obtain the cardiac time intervals including the isovolumic contraction time (IVCT), isovolumic relaxation time (IVRT) and ejection time (ET). The myocardial performance index (MPI) is defined as [(IVCT+IVRT)/ET]. Our aim was to investigate if the cardiac time intervals can be used to predict heart failure (HF) in the general population. Methods and results: A total of 1915 participants (mean age 58 ± 16 years, 42% male) from the general population (The Copenhagen City Heart Study) underwent a health examination including TDI-echocardiography. The primary endpoint was incident HF. Participants with a history of HF were excluded ( n  = 23). During a median follow-up time of 16 years, 172 (9%) participants were diagnosed with incident HF. The risk of HF increased with 24% per 10 ms increase in IVCT (per 10 ms increase: HR 1.24; 95%CI (1.14–1.36), p  < 0.001). The association remained significant after adjusting for age, sex, hypertension, diabetes, previous ischemic heart disease, diastolic blood pressure, heart rate, body mass index, eGFR, proBNP, LVEF <50%, s′, LAVI, and E/e′ (per 10 ms increase: HR 1.13; 95% CI (1.00–1.27), p  = 0.045). A significant association was found between MPI and HF both in unadjusted and adjusted models (per 0.1 increase: HR 6.93; 95% CI (1.63–29.31), p  = 0.009). No associations between the IVRT or ET and HF remained significant after multivariable adjustment. Conclusion: In the general population the IVCT provides novel and independent prognostic information on the long-term risk of incident HF. Highlights: Color TDI M-mode is a novel method to obtain cardiac time intervals including IVCT. The IVCT is a novel and independent predictor of HF in the general population. The association remained significant even after multivariable adjustment.